Les interactions entre la dramaturgie et la conception des images au Moyen Âge. - Claire Bonnotte (Perspectives Médiévales)
With the help of Emile Mâle’s (1862-1954) pioneer researches on art history, our knowledge about western medieval images has improved during the last century thanks to the interesting study of dramaturgy (xith-xvith centuries). Since the 1920’s, the iconography of the apparition of Christ in Emmaus (Luke, 24, 13-35) is one of the examples currently chosen by historiography in order to illustrate interactions between images and liturgical dramas. In the light of this observation, I reopened this file with the aim of identifying in a better way the relationships between these two ways of expressions. If this study has been often led in liturgical dramas’ field, I have opened it to Mystères de la Passion, in which the apparition of Christ in Emmaus knew important developments. Restricted to French literary and iconographical productions, my investigation leads nevertheless to mixed results. With the exception of images taken from rare illustrated theatre manuscripts, the iconography is most of the time quite different from the corresponding dramatic texts.